Excessive premature mortality among children with cerebral palsy in rural Uganda: A longitudinal, population-based study. - Lukia H, Namaganda; Rita, Almeida; Dan, Kajungu; Fred, Wabwire-Mangen; Stefan, Peterson; Carin, Andrews; Ann, Christin Eliasson; Angelina, Kakooza-Mwesige; Hans, Forssberg (Public Library of Science, 2020)
BackgroundStudies from high-income countries reported reduced life expectancy in children with cerebral palsy (CP), while no population-based study has evaluated mortality of children with CP in sub-Saharan Africa. This study aimed to estimate the mortality rate (MR) of children with CP in a rural region of Uganda and identify risk factors and causes of death (CODs).Methods and findingsThis population-based, longitudinal cohort study was based on data from Iganga-Mayuge Health and Demographic Surveillance System in eastern Uganda. We identified 97 children (aged 2-17 years) with CP in 2015, whom we followed to 2019. They were compared with an age-matched cohort from the general population (n = 41 319). MRs, MR ratios (MRRs), hazard ratios (HRs), and immediate CODs were determined. MR was 3952 per 100 000 person years (95% CI 2212-6519) in children with CP and 137 per 100 000 person years (95% CI 117-159) in the general population. Standardized MRR was 25·3 in the CP cohort, compared with the general population. In children with CP, risk of death was higher in those with severe gross motor impairments than in those with milder impairments (HR 6·8; p = 0·007) and in those with severe malnutrition than in those less malnourished (HR = 3·7; p = 0·052). MR was higher in females in the CP cohort, with a higher MRR in females (53·0; 95% CI 26·4-106·3) than in males (16·3; 95% CI 7·2-37·2). Age had no significant effect on MR in the CP cohort, but MRR was higher at 10-18 years (39·6; 95% CI 14·2-110·0) than at 2-6 years (21·0; 95% CI 10·2-43·2). Anaemia, malaria, and other infections were the most common CODs in the CP cohort.ConclusionsRisk of premature death was excessively high in children with CP in rural sub-Saharan Africa, especially in those with severe motor impairments or malnutrition. While global childhood mortality has significantly decreased during recent decades, this observed excessive mortality is a hidden humanitarian crisis that needs to be addressed. 7CITATIONS7 total citations on Dimensions.
Keywords: Medicine ,Science